Comparison of the Efficacy of Stretching and Isometric Exercises Versus Manual Traction and Isometric Exercises on Knee Pain and Functional Activities in Tibiofemoral Osteoarthritis - Chandra Mounika Indana; Narasinga Rao K (RGUHS Journal of Physiotherapy)
Background Osteoarthritis OA is a common degenerative condition characterized by pain functional impairment and reduced quality of life. Outcome measures commonly used include the Visual Analogue Scale VAS for pain assessment and the Western Ontario and McMaster Universities Osteoarthritis Index WOMAC for evaluating pain stiffness and physical function.Objectives The objectives were to evaluate the efficacy of stretching and manual traction combined with isometric exercises in improving pain and functional activities and to compare their efficacy in subjects with tibiofemoral osteoarthritis.Methods This experimental study was conducted on 30 subjects fulfilling the inclusion criteria. The subjects were divided into two groups Stretching with isometric exercises n15 and Manual traction with isometric exercises n15. Both the groups received treatment and the outcomes were measured after three weeks of treatment. Paired t-test was used to analyze significance within the groups and unpaired t-test was used to compare both the groups.Results The results showed a statistically significant improvement in pain and functional activity P0.01 in both the groups. Intergroup analysis showed significant difference in all the variables P lt0.05 in manual traction group compared to stretching group. The level of significance was set at P lt0.05.Conclusion Both the groups demonstrated improvement after three weeks of intervention but the manual traction with isometric exercises group showed better mean difference and percentage improvement compared to the other group in all the tested variables.